Viability of the novel process of indirect laser brazing - M. Y., Yuserny; M. H., Aiman; M. M., Quazi; M., Ishak; J., Shamini (OCP Science imprint, 2021)
Brazing is a 5000 year old joining process which faced still with the advanced joining challenges that exist today [1]. In laser brazing components are joined together by heating above the melting point of a filler metal placed between them. It provides unique advantages over other joining methods, including the ability to joint dissimilar material. Indirect laser brazing is a novel process which able to joint dissimilar metals with minimal formation of a brittle intermetallic compound (IMC) layer than conventional furnace brazing. In this study the viability of indirect laser brazing process was investigated between Ti6Al4V and 316L stainless steel.